2020
DOI: 10.3390/ijms21249737
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics, Prebiotics and Synbiotics—A Promising Strategy in Prevention and Treatment of Cardiovascular Diseases?

Abstract: Recent evidence suggests that probiotics, prebiotics and synbiotics may serve as important dietary components in the prevention (especially) and treatment of cardiovascular diseases (CVD), but the recommendations for their use are often based on brief reports and small clinical studies. This review evaluates the current literature on the correlation between CVD and probiotics, prebiotics and synbiotics. Although research on probiotics, prebiotics and synbiotics has grown exponentially in recent years, particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 84 publications
0
39
0
Order By: Relevance
“…Cardiovascular diseases involve the heart or blood vessels, the most well-known being coronary artery disease, stroke, hypertensive heart disease, cardiomyopathy, venous thrombosis, arrhythmia, and thromboembolic disease. CVD is a growing global health problem [7][8][9]. In 2015, 18 million deaths were attributed to cardiovascular diseases, accounting for approximately one-third of all-cause deaths and representing an increase of 12.5% from 2005.…”
Section: Cardiovascular Disease: Risk Factors and The Mechanism Of Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Cardiovascular diseases involve the heart or blood vessels, the most well-known being coronary artery disease, stroke, hypertensive heart disease, cardiomyopathy, venous thrombosis, arrhythmia, and thromboembolic disease. CVD is a growing global health problem [7][8][9]. In 2015, 18 million deaths were attributed to cardiovascular diseases, accounting for approximately one-third of all-cause deaths and representing an increase of 12.5% from 2005.…”
Section: Cardiovascular Disease: Risk Factors and The Mechanism Of Developmentmentioning
confidence: 99%
“…Prebiotics represent substances most used to maintain a normal gut microbiota and restore its equilibrium when homeostasis is affected [53][54][55]. Prebiotics contain only substances which stimulate microorganism growth; there are no bacteria in their composition [9]. These substances can be obtained from various sources, including soybeans, raw oats.…”
Section: Probiotics and Prebiotics: General Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies focused (153)(154)(155). Besides, adherence to Mediterranean diet also can modulate intima-media thickness and atherosclerotic plaques (156)(157)(158)(159). Some scientists have found that MeDiet acted on the atherosclerotic inflammatory process by downregulating proinflammatory biomarkers and upregulating biomarkers associated with the stability of plaque.…”
Section: Therapy Daily Lifestyle Gut Microbiota and Atherosclerosismentioning
confidence: 99%